Teaching Practice of Engineering Management Course for Engineering Education Certification under Background of Artificial Intelligence - Dan Wang; Fengyi Han; Qi Zhao; Yinyin Lv (International Transactions on Electrical Energy Systems)
With the advancement of China’s industrial construction, the field of engineering management has also attracted more attention. However, China’s engineering management major is currently in a growing stage due to the issue of the opening years, and the teaching and practice setting of each course is also in an immature stage, which makes China’s engineering management majors present more and more problems. The truancy rate has been increasing year by year, the students’ dominant position in the class has become objectified, and their trust in teachers has decreased. Students’ learning shows the characteristics of individualization and diversity. Higher requirements are put forward for teachers’ teaching quality, and schools lack an effective supervision mechanism. In order to solve these problems better, it is imperative to reform and innovate the course teaching of engineering management majors. The core of engineering education accreditation is to confirm that engineering graduates meet established quality standards recognized by the industry. It is a unique method to test whether the course teaching of engineering management majors is qualified and attracts many scholars to discuss it. Engineering education accreditation has attracted many scholars to discuss it because it is a unique means to test the qualifications of engineering management students’ course teaching. This study was based on an in-depth exploration of the teaching practice of engineering management courses and combines artificial intelligence with an engineering education certification. Through the research and analysis of colleges and universities, the research finally showed that the engineering management professional course teaching of engineering education certification under the background of artificial intelligence can promote the attendance of students in school by about 20%. The achievement of course teaching objectives has increased by about 13% and the comprehensive ability level of graduates has increased by about 8%. It improved the overall level of students and the teaching quality and efficiency of engineering management courses and also promoted the development of college education so that today’s engineering management graduates can better meet the needs of today’s society.